Towards an understanding of gender and capital in constituting biotechnologies in agriculture - Bryant, L.; Pini, Barbara (Blackwell Publishing, 2006)
A compelling body of international literature now exists on the political economy of biotechnology. This work has used capital as a lens through which to view the increasing economic importance of biotechnologies to the agricultural sector. It has, however, given little attention to gender. The purpose of this article is to argue for the significance of gender in studies of agricultural biotechnology, that is, to posit that it is not just capital, but the intersection between capital and gender that informs the application, creation and regulation of agricultural biotechnologies.